Climate Politics and Global Governance: Assessing the Role of International Agreements in Environmental Policy-Making - MIR AADIL BASHIR (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research paper explores the intricate interplay between climate politics and global governance, focusing specifically on the role of international agreements in shaping environmental policy-making. As climate change transcends national boundaries, it has become a pivotal issue requiring coordinated global action. The study examines the evolution of major climate agreements, such as the Kyoto Protocol and the Paris Agreement, and evaluates their impact on global environmental governance. By analyzing the contributions and limitations of state and non-state actors, global institutions, and multilateral frameworks, the paper highlights both the progress achieved and the persistent challenges in implementing climate commitments. Emphasis is placed on the dynamics between developed and developing nations, issues of climate justice, and the need for equitable, inclusive, and enforceable global mechanisms. The paper concludes by proposing strategic pathways for enhancing international cooperation and effectiveness in climate governance, underscoring the urgency of collective action in the face of escalating environmental threats.